Distribusi spasial kualitas perairan dan hubungannya dengan aktifitas budidaya perikanan di Teluk Lampung - Budhi Agung Prasetyo; Muawanah Muawanah; Lutfi Mardianto; Muhammad Zainuddin Lubis (Journal of Science and Applicative Technology, 2022)
Coastal water is water areas that receive much input of organic matter originating from human activities on land. Anthropogenic activities such as marine aquaculture in Teluk Lampung impact water quality on that waters. This study was conducted to determine the distribution of water quality around Teluk Lampung and its correlations to marine aquaculture activities. The analysis carried out in this study is spatial analysis to determine the spatial distribution of water quality in three focus area, namely Teluk Hurun (HB), Selatan Teluk Hurun (SHB) dan Pantai Sari Ringgung (SRB) as part of Teluk Lampung. In addition to spatial analysis, principal component analysis (PCA) was also carried out to determine water quality as a variable and its correlation to each area. Based on the results of this study, the spatial distribution of water quality varies based on the human activities type in each area. Based on the results of principal component analysis, it is known that the variability of several water quality variables also correlates with the human activities types, such as marine aquaculture and beach tourism.